Efektivitas Kombinasi Vankomisin dan Vitamin C terhadap Pertumbuhan MRSA (Methicillin Resistant Staphylococcus aureus) (Effectiveness of Vancomycin and Vitamin C Combination on MRSA (Methicillin Resistant Staphylococcus aureus) Growth) - Ulin Nuha Jazmin; Dini Agustina; Rony Prasetyo (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Nephrotoxicity due to prolonged use of vancomycin becomes a big issue in patients with MRSA infections and the use of vitamin C has been proved to decrease this side effect. Vitamin C with its combination with antibiotic will halt MRSA growth by forming Reactive Oxygen Species (ROS). This study aimed to determine the effect of vancomycin and vitamin C combination in order to halt the MRSA growth and the minimum concentration of vitamin C which can decrease the Minimum Inhibitory Concentration (MIC) of vancomycin. This study used a quasi experimental design with 7 groups, 1 as negative control which only given vancomycin and 6 other groups which given vancomycin and vitamin C with following concentration 0,4; 0,8; 1,6; 3,2; 6,4; and 12,8 mg/mL. We used microdilution method with 4 repetitions to measure the MIC value. This study revealed that there were no difference between control and other groups, the MIC of vancomycin is 1 µg/mL. Combination effect was measured by Fractional Inhibitory Concentration Index (FICI) calculation which showed indifferent effect to all groups. This study concluded that combination of vancomycin and vitamin C effect has no difference with control group and by adding vitamin C until 12,8 mg/mL did not decrease MRSA growth. Keywords: MRSA, vancomycin, vitamin C, Minimum Inhibitory Concentration (MIC)